Salvage Stories, Preserving Narratives, and Museum Ships - Sawyer, Andrew (Museum and Society, 2015)
<span style="color: #292526; line-height: 115%; font-family: 'Arial','sans-serif'; font-size: 9pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-ansi-language: EN-GB; mso-bidi-language: AR-SA;">Preserved ships and other vessels are associated with a historiography, in Europe at least, which is still marked by parochialism, antiquarianism, and celebratory narrative. Many evidence difficult histories, and they are also extremely expensive to preserve. Yet, they are clearly valued, as nations in Europe invest heavily in them. This survey examines a range of European examples as sites of cultural, political and national identity. An analytical framework foregrounding the role of narrative and story reveals three aspects to these exhibits: explicit stories connected with specific nations, often reinforcing broader, sometimes implicit, national narratives; and a teleological sequence of loss, recovery and preservation, influenced by nationality, but very similar in form across Europe